Menggagas Fikih Tasamuh di Tengah Masyarakat Multikultural - Ridwan Ridwan (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2009)
An accommodative Islamic law is needed in this multicultural society. Ijtihad is an inner dynamic which guides the changes. Fiqh as the reflection of ulama responds the pluralism towards the problems in the society.